Penguatan Kesadaran Hidup Berkoperasi dalam Meningkatkan Partisipasi Anggota pada KSP Kopdit Pintu Air Cabang Maumere - Loe, Elisabeth Agustina; Mitan, Wilhelmina; Diliana, Siktania Maria (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to find out how to strengthen awareness of cooperative life in increasing member participation in KSP Kopdit Pintu Air Maumere Branch. To identify problems, this research uses qualitative research. The data collection techniques use observation, interviews and documentation. It can be concluded that the factors that influence the decline in member participation are caused by members' lack of knowledge in cooperative life, economic constraints, and fraud or abuse. Efforts to increase member participation include providing education and training, open communication, and participation in decision making. Keywords : Participation of Members of KSP Kopdit Pintu Air Maumere Branch, Strengthening Awareness of Cooperative Life